Challenges of Studying Languages and Cultures in the Multicultural World - Arifi Teuta (SEEU Review)
Multilingualism and multiculturalism have been integral aspects of human civilization throughout history, yet they continue to present significant communicative challenges. Jacques Derrida likened the effort to understand others through translation to the reconstruction of the Tower of Babel, emphasizing the difficulty of finding precise expressions across different languages and cultural contexts (Derrida, 1985). This paper argues that learning and studying diverse languages are essential not only for thriving in a multicultural world but also for fostering peace and mutual trust in an increasingly interconnected global society. The central thesis posits that global development trends and intercultural communication should be embraced as opportunities to promote multilingualism rather than as competitive barriers. Drawing on interculturalism theories by scholars such as Zapata-Barrero, Kymlicka, and Vertovec, this paper underscores the importance of creating a superdiverse world where multilingualism ensures cultural-linguistic inclusivity. The study further highlights the necessity of pragmatic approaches to integrate linguistic diversity into global and local policies, particularly in regions like Southeast Europe. By doing so, it seeks to position language studies as crucial to the era of globalization.